2018
DOI: 10.20473/fmi.v54i4.10708
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Extended Spectrum Beta-Lactamase (ESBL) Producing Gut Bacterial Flora Among Patients in Dr. Soetomo Hospital and Primary Health Centre in Surabaya

Abstract: The extended-spectrum b-lactamase (ESBL) producer bacteria until now were mostly identified in hospital environment. The aim of this study was to analyze the prevalence of ESBL-producing gut flora and distribution of ESBL encoding genes between hospitalized patient in Tropical Wards of Dr. Soetomo Hospital and patient from a primary health centre (PHC) as community environment in Surabaya. Thiry rectal swab samples from hospital of Dr. Soetomo patients and from PHC (60 samples in total) were collected for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 25 publications
1
3
0
1
Order By: Relevance
“…The gene type of bla TEM has been reported to be responsible for 90% of ampicillin resistance in E. coli, while this study also showed that the isolates were resistant to ampicillin with 50% (15/30) detected bla TEM [18]. Multiple genes patterns of bla TEM and bla CTX-M were predominantly found in this study, which is consistent with previous studies in Surabaya, conducted by Naelasari et al (24%) and in Denpasar, conducted by Fatmawati et al (15.5%) [19,20] This pattern was also consistent with another study in Iraq, reported by Pose et al that bla TEM and bla CTX-M were dominant (30.9%). Such molecular patterns also showed similar antibiotic sensitivity patterns, which were mostly sensitive to meropenem and amikacin [21].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The gene type of bla TEM has been reported to be responsible for 90% of ampicillin resistance in E. coli, while this study also showed that the isolates were resistant to ampicillin with 50% (15/30) detected bla TEM [18]. Multiple genes patterns of bla TEM and bla CTX-M were predominantly found in this study, which is consistent with previous studies in Surabaya, conducted by Naelasari et al (24%) and in Denpasar, conducted by Fatmawati et al (15.5%) [19,20] This pattern was also consistent with another study in Iraq, reported by Pose et al that bla TEM and bla CTX-M were dominant (30.9%). Such molecular patterns also showed similar antibiotic sensitivity patterns, which were mostly sensitive to meropenem and amikacin [21].…”
Section: Discussionsupporting
confidence: 91%
“…The prevalence of ESBLs type, bla CTX-M was still more dominant than other types in Surabaya that reported 80% and 94.5% in E. coli and 55.6% in K. pneumonia [19,22]. Other studies in Singapore, Vietnam, and Thailand also showed a prominent spreading of CTX-M type ESBLs.…”
Section: Discussionmentioning
confidence: 97%
“…ESBL ESBL is produced by gram-negative bacteria, for example the family Enterobacteriaceae which is a normal intestinal flora where this bacterium has been resistant to beta lactam antibiotics and is one of the main causes of bacterial infections in hospitals or in the community. 16…”
Section: Resultsmentioning
confidence: 99%
“…ESBL-producing bacteria were confirmed using DDST (Double Disk Synergy Test) using antibiotic disc of ceftriaxon, cefotaxim, cefepim and aztreonam with amoxicillin-clavulanic acid at the center of the plate. (9) The identification was performed at Microbiology Laboratory, Dr. Soetomo General Hospital Surabaya. Data analysis was conducted using SPSS Statistical Software version 20.…”
Section: Methodsmentioning
confidence: 99%